PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORT TERHADAP PROFITABILITAS PERUSAHAAN STUDI KASUS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DALAM BURSA EFEK INDONESIA - Adhima, SE, Mochammad Fauzan; Hariadi, SE., M.Ec., Ak., Bambang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims to obtain empirical evidence about the effect of disclosure Sustainability Report (SR), the disclosure of environmental performance, social performance and disclosure on the profitability of the company. Disclosure Sustainability Report (SR), the disclosure of environmental performance and social performance disclosure was measured using the Global Reporting Initiative Guidelines G-3 (G-3 GRI Guidelines). Profitability measured using Return on Assets (ROA). The population in this study is manufacturing companies listed in the Indonesia Stock Exchange (IDX) during the period 2009-2011. Total sample is 26 firms determined by the method of purposive sampling. Data analysis was performed by testing the classical assumptions and hypothesis testing using multiple linear regression analysis. The results of this study indicate that the disclosure of Sustainability Report (SR) and the disclosure of environmental performance have significant positive impact on Return on Assets (ROA). Meanwhile, the disclosure of social performance has significant negative effect on Return on Assets (ROA). Keywords: Disclosure Sustainability Report (SR), Disclosure of environmental performance, social performance disclosure, Profitability, Return on Assets (ROA).